2016
DOI: 10.4103/0300-1652.188337
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a single mid-trimester measurement of plasminogen activator Type 1 and fibronectin to predict preeclampsia in pregnancy

Abstract: Background:Preeclampsia (PE) is the second most common cause of maternal death after obstetric hemorrhage in Africa, a resource-limited region. This study was designed to examine the potential usefulness of a single screening plasma plasminogen activator inhibitor-1 (PAI-1) and fibronectin (FN) level for the prediction of PE in pregnant women.Materials and Methods:In a cohort of 180 pregnant women who were normotensive at baseline, venous blood samples were obtained before 20 weeks of gestation for the assay o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The characteristics of the cross-sectional, 9 , 35 , 36 , 40 , 42 , 46 89 prospective, or retrospective cohort and longitudinal studies 5 , 10 , 37 39 , 41 , 90 103 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the cross-sectional, 9 , 35 , 36 , 40 , 42 , 46 89 prospective, or retrospective cohort and longitudinal studies 5 , 10 , 37 39 , 41 , 90 103 ...…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the cross-sectional, 9,35,36,40,42, prospective, or retrospective cohort and longitudinal studies 5,10,[37][38][39]41,[90][91][92][93][94][95][96][97][98][99][100][101][102][103] included in this review from 19 Sub-Saharan African countries are summarized in Table 1. The majority of studies were conducted in Nigeria, Ethiopia, and Tanzania, which are 21, 16, and 6, respectively.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The authors concluded that second-trimester assessment of FN levels in maternal plasma was not found to be useful in predicting PE. 42 Paneva-Masin et al also concluded that the measurement of plasma FN might be of diagnostic value in PE but could not be considered a useful predictor for PE. 43 In the abovementioned previous reports, higher FN in the secondtrimester maternal plasma of PE pregnancies was observed in most reports except one report of Ajibola et al 42 17,35,36,[40][41][42] Five reports suggested that FN had predictive value for PE, while the other three reports concluded that FN was not a useful predictor for PE.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of plasma FN was very low (2-5 mg/L) in the two reports using ELISA. 36,42 Even in reports using the same method, different instruments and commercial kits were used. Different methods, instruments, and kits detected different FN variants.…”
Section: Discussionmentioning
confidence: 99%
“…We were able to overcome this drawback by limiting our recruitment to women with early onset PE. However, Ajibola's group failed to demonstrate any significant differences in plasma fibronectin levels between PE and normotensive pregnant women (16). The potential utility of fibronectin as a biomarker for PE prediction received some attention although concerns increased surrounding its sensitivity (17).…”
Section: Discussionmentioning
confidence: 99%